2022
DOI: 10.3389/fendo.2022.1051797
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and its derived SCFAs regulate the HPGA to reverse obesity-induced precocious puberty in female rats

Abstract: The intestinal microbiota and its derived short-chain fatty acids (SCFAs) can reverse obesity and obesity-related metabolic diseases, but whether it has an effect on obesity complicated by precocious puberty and its potential mechanism need to be further understood. The purpose of this study was to investigate the effect of the gut microbiota and its derived short-chain fatty acids (SCFAs) on obesity-induced precocious puberty rats and their regulatory mechanisms. We constructed obesity-induced precocious pube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In this study, Wang et al found that microbiota-derived SCFAs reversed the high-fat-induced obesity-mediated precocious puberty, with mechanisms of impact on the HPGA (14). Hence, a novel remote brake (gut microbiota-SCFA) of precocious puberty was characterized.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…In this study, Wang et al found that microbiota-derived SCFAs reversed the high-fat-induced obesity-mediated precocious puberty, with mechanisms of impact on the HPGA (14). Hence, a novel remote brake (gut microbiota-SCFA) of precocious puberty was characterized.…”
Section: Discussionmentioning
confidence: 76%
“…The authors ( 14 ) firstly confirmed that treatment of HFD after weaning induced obesity and precocious puberty in female rats and upregulated HPGA gene expressions, including Kiss1 (kisspeptin-1), GPR54 (G protein-coupled receptor 54, Kiss1R), GnRH (gonadotropin-releasing hormone), Erα (estrogen receptor α) in the hypothalamus, GnRHR (gonadotropin-releasing hormone receptor) in the pituitary, and LHR (luteinizing receptor), FSHR (follicle-stimulating hormone receptor), and Erα in the ovary. In view of flora, the authors found that HFD significantly changed the composition of intestinal microbiota, with increased levels of Bacteroidota, Proteobacteria, and Verrucomicrobiota but decreased levels of Firmicutes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations